Recent developments in international banking and finance : vol iv and v - Khoury, Sarkis J.; University of California, Riverside (Armsterdam. : Elsevier, 1987)
Papers from symposia sponsored by the Graduate School of Management, University of California at Riverside, the Philadelphia Stock Exchange and Asian Finance.
Title varies slightly.
Papers from symposia sponsored by the Graduate School of Management, University of California at Riverside, 1986-
Published: Chicago : Probus, 1989; Amsterdam : North-Holland, 1991; Cambridge, Mass. : Blackwell, 1992-
includes references
opc 09/01/17
Loans
Keywords: International finance; Banks and banking, International; Banking and finance; Recent developments - banking